Penerapan Permainan Tradisional Boy-boyan Untuk Meningkatkan Minat Belajar Pendidikan Jasmani Pada Siswa SMP Negeri 2 Majalaya Karawang - Ibrahim Mohammad; Ine Rahayu Purwaningsih; Ardawi Sumarno (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of making this thesis is to answer the formulation of the problem in the research, namely whether there is an increase in interest in learning physical education through traditional boy-boyan games in students, is there an impact of traditional boy-boyan games on increasing interest in learning physical education in students. The problem of this study is that there are students who feel bored in attending physical education lessons. This research is a quantitative research with experimental methods and uses a pretest-posttest control group design design. The sampling technique uses cluster sampling technique. The instrument used is a likert scale questionnaire questionnaire.There are three stages in this study, namely pretest, treatment and posttest. Treatment was conducted sixteen times. From the pretest and posttest results, there was an increase from the initial average of 74.25, a significant value was obtained from the pretest results, namely 0.290 while the posttest value was 0.420 from these results, it is said that both are normally distributed because the significant value is more than 5% or from 0.05.